2013
DOI: 10.1128/iai.01332-12
|View full text |Cite
|
Sign up to set email alerts
|

Roles of STAT3 in Protein Secretion Pathways during the Acute-Phase Response

Abstract: The acute-phase response is characteristic of perhaps all infections, including bacterial pneumonia. In conjunction with the acute-phase response, additional biological pathways are induced in the liver and are dependent on the transcription factors STAT3 and NF-B, but these responses are poorly understood. Here, we demonstrate that pneumococcal pneumonia and other severe infections increase expression of multiple components of the cellular secretory machinery in the mouse liver, including the endoplasmic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Recently, our laboratory has also shown that the APR is necessary for survival during a gram-positive Streptococcus pneumoniae infection (11). Indeed, these studies and others have now revealed over 1,000 gene changes and numerous biological processes in the liver that are altered during pneumonia, any or all of which could influence disease outcome (6,11,36). In those studies, CRE 1 mice showed decreased complement deposition and opsonophagocytosis of pneumococcus, leading to increased bacteremia, suggesting that one function of the APR is to limit dissemination of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory has also shown that the APR is necessary for survival during a gram-positive Streptococcus pneumoniae infection (11). Indeed, these studies and others have now revealed over 1,000 gene changes and numerous biological processes in the liver that are altered during pneumonia, any or all of which could influence disease outcome (6,11,36). In those studies, CRE 1 mice showed decreased complement deposition and opsonophagocytosis of pneumococcus, leading to increased bacteremia, suggesting that one function of the APR is to limit dissemination of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, E. coli pneumonia models induce large amounts of lung injury necessary to induce plasma protein (and thus APP) extravasation into the airspaces, which is key in understanding how the liver response to sepsis can directly influence local lung defense. Because liver STAT3 activation is required for maximal APR induction (24,25,30,31), we measured the concentrations of two representative, circulating APPs: serum amyloid A (SAA) and serum amyloid P (SAP). In WT mice, the concentrations of both SAA and SAP in serum were induced dramatically above baseline with LPS pretreatment alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Induced by the host defense cytokines tumor necrosis factor alpha (TNF-␣), interleukin-1 (IL-1), and IL-6 (20), the APR is characterized by significant changes in circulating levels of acute-phase proteins (APPs) (19,21,22). While it is well appreciated that sepsis can cause pulmonary immunosuppression and pneumonia susceptibility (5, 7-15), it is unclear whether or how preexisting liver activation (i.e., sepsis-induced APR) modulates subsequent responses to local lung infections.Signal transducer and activator of transcription-3 (STAT3) is one of two transcription factors (along with NF-B RelA) required for induction of a strong hepatic APR during pneumonia (23)(24)(25). Several lines of evidence implicate beneficial roles for liver-derived APPs during pneumonia (26)(27)(28)(29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intrapulmonary delivery of bacteria or bacterial products elicits a rapid and robust acute phase response (25, 37, 78, 79). The liver alters expression of more than a thousand genes during pneumococcal pneumonia (79).…”
Section: Resistance: Cell-specific Roles That Initiate Direct and Amentioning
confidence: 99%